2021
DOI: 10.3389/fphar.2021.727707
|View full text |Cite
|
Sign up to set email alerts
|

The Prognostic Effect of Dexamethasone on Patients With Glioblastoma: A Systematic Review and Meta-Analysis

Abstract: Background: Dexamethasone (DEX) is widely adopted to reduce tumor-associated edema in glioblastoma (GBM) patients despite its side effects. However, the benefits of using DEX in GBM patients remains elusive.Methods: In this study, we performed a comprehensive meta-analysis to address this concern. We searched the relevant studies from PubMed, Web of Science, and EMBASE databases, and then applied random or fixed-effects models to generate estimated summary hazard radios (HRs) and the 95% confidence intervals (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 25 publications
1
11
0
1
Order By: Relevance
“…20 Likewise, a meta-analysis including 2230 adult glioblastoma patients partly confirmed an association of DM application with poor treatment outcome. 21 However, there is no significant data derived from pediatric cohorts available to this day.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…20 Likewise, a meta-analysis including 2230 adult glioblastoma patients partly confirmed an association of DM application with poor treatment outcome. 21 However, there is no significant data derived from pediatric cohorts available to this day.…”
Section: Discussionmentioning
confidence: 99%
“…While the effects of DM on cell growth and OS in adult glioma remains controversial, independent studies, as well as a meta-analysis partly confirmed association of a poor treatment outcome with use of DM in adult glioma. 20,21 To our knowledge, no significant clinical data regarding the impact of DM on progression-free survival (PFS) and OS in pLGG has been published to this day.…”
Section: Introductionmentioning
confidence: 99%
“…anohe command of the R package of “gemtc” was utilized by reporting the heterogeneity variance parameter I 2 . I 2 > 50% was regarded as significant heterogeneity, and the random effects models would be utilized; otherwise the fixed effect models would be utilized ( Ma et al, 2021 ; Zhou et al, 2021 ). Sensitivity analysis was also conducted to examine the robustness of our results.…”
Section: Methodsmentioning
confidence: 99%
“…Perioperative dexamethasone use leads to its dependence during adjuvant therapy, which lowers survival. Retrospective analyses of large cohorts and post hoc analysis of two large, multicenter, phase 3 RCTs show that GBM patients treated with dexamethasone during chemoradiation have lower survival (32)(33)(34)(35). Thus, the use of dexamethasone during chemoradiation has declined (36).…”
Section: Long-term Harms Of Dexamethasonementioning
confidence: 99%